2015
DOI: 10.5194/angeo-33-1301-2015
|View full text |Cite
|
Sign up to set email alerts
|

A physical explanation for the magnetic decrease ahead of dipolarization fronts

Abstract: Abstract.Recent studies have shown that the ambient plasma in the near-Earth magnetotail can be compressed by the arrival of a dipolarization front (DF). In this paper we study the variations in the characteristics of currents flowing in this compressed region ahead of the DF, particularly the changes in the cross-tail current, using observations from the THEMIS satellites. Since we do not know whether the changes in the cross-tail current lead to a field-aligned current formation or just form a current loop i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 58 publications
7
44
0
Order By: Relevance
“…To reveal the unbiased pattern, please refer to and L DT ≈ 3.0 R E . Second, for both regions, a dipolar feature in the Z component of the magnetic field can be observed as has already been reported by others (Angelopoulos et al, 1992;Ohtani et al, 2004;Runov et al, 2011;Liu et al, 2013;Yao et al, 2015). Third, the density variation is different for the two regions.…”
Section: Superposed Epoch Analysis Of Plasma Quantitiessupporting
confidence: 72%
See 2 more Smart Citations
“…To reveal the unbiased pattern, please refer to and L DT ≈ 3.0 R E . Second, for both regions, a dipolar feature in the Z component of the magnetic field can be observed as has already been reported by others (Angelopoulos et al, 1992;Ohtani et al, 2004;Runov et al, 2011;Liu et al, 2013;Yao et al, 2015). Third, the density variation is different for the two regions.…”
Section: Superposed Epoch Analysis Of Plasma Quantitiessupporting
confidence: 72%
“…Recently, Schmid et al (2015) performed statistical studies on dipolarization fronts and plasma flows in THEMIS data and hypothesize on the development of such events. Yao et al (2015) used the list of Liu et al (2013) to try to physically explain the dipolarization feature of fast flows. Runov et al (2015) showed that the characteristic timescale of the flux transport enhancements does not depend on geocentric distance and is around 40-60 s. Most recently, Wang et al (2016) found evidence of compressible fluctuations during bursty bulk flows in the plasma sheet.…”
Section: Frühauff and K-h Glassmeier: Magnetotail Fast Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) As shown previously in the literature, near-earth instabilities and reconnection usually take place in thin current sheet conditions (Büchner and Kuska 1999;Drake et al 1994;Nakamura et al 2006;Birn 1993, 1999). (2) It is also often reported that both reconnection and plasma instability are associated with magnetic dipolarization Lui et al 2008b;Yao et al 2013bYao et al , 2015; (3) Reconnection and reconnection outflows may also directly trigger a pseudo-substorm (or very small substorm) (Pu et al 2010;Yao et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, a very large number of DFBs is required to account for the magnetic flux in the near-Earth dipolarization for a moderate size substorm. This result was reached by Lui (2015) and Yao et al (2015).…”
Section: Summary and Discussionmentioning
confidence: 68%